Measuring entrepreneurial orientation of Bahir Dar University students - Girma Tilahun Weldehawartiat; Mastewal Birhanu Mergiaw; Mahlet Haimanot Berhanu; Chris Friedrich (Cogent Business & Management)
The purpose of this research was to examine entrepreneurial orientation of Bahir Dar University (BDU) students as research. The paper reports on experimental research undertaken to evaluate the entrepreneurship course offered at Bahir Dar University. 183 undergraduate students were recruited using stratified sampling across colleges for the study. A standardized questionnaire adopted from Entrepreneurial Attitude Orientation (EAO) scale was used as a data collection instrument measuring four constructs: achievement, innovation, perceived personal control, and perceived self-esteem in business. A pre-test was given for the sample students before the course began. Then, the course was given for a semester, after which a post-test was given to 176 students since 7 students had withdrawn from the study. The findings of the study revealed that, except in innovation, a non-significant contribution was found in the remaining three constructs. Educators and curricula experts might get deep insight about what aspects of entrepreneurship course would bring about entrepreneurial inclination in the students’ minds. Concerned management bodies of the University on entrepreneurship training and education programs could also use the findings to make required interventions in the form of support, revision, and encouragement of the programs.